The Biopolitical Logics of Settler Colonialism and Disruptive Relationality. (February 2017) - Dietrich, René
This essay argues that the biopolitical logics of settler colonialism function according to a naturalization in Western thought of politics as a project of hierarchically ordering life in relation to the sphere of politics. Significantly, such a mode of thinking discredits socio-political orders that operate on the basis of a non-hierarchical place-based relationality of all life forms including the land. Through a reading of Foucault and Agamben in their use of Aristotle, I want to show how hierarchy as a principle of the political is already implemented in the premise they draw upon for analyzing the biopolitical. In the same way it remains unrecognized in their analysis of biopolitics, this principle also becomes operative within settler colonial logics of life and land. Recently, however, Indigenous scholars and writers have mobilized relationality in its formative characteristic for Indigenous polities and politics as strategy to disrupt biopolitical logics and denaturalize settler colonial rule, which I want to show through engaging Daniel Heath Justice's Indigenous fantasy trilogy The Way of Thorn and Thunder: The Kynship Chronicles as a site of disruptive relationality and political knowledge production.